CARACTERIZAÇÃO FOLICULAR E DESEMPENHO À IATF DE NOVILHAS TRADICIONAIS E PRECOCES DA RAÇA NELORE - ORUÊ, Andrey Makálister Souza; MELO STERZA, Fabiana de Andrade Melo; FERREIRA, Mariane Gabriela César Ribeiro; CARVALHO, Marcelo da Silva de; LIMA, Thais Ferreira; OLIVEIRA, Arianny Lima Ferreira (ANAIS DO ENIC, 2025)
-